2021
DOI: 10.1186/s12896-021-00688-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity activities and chemical characteristics of exopolysaccharides and intracellular polysaccharides of Physarum polycephalum microplasmodia

Abstract: Background Microbial polysaccharides have been reported to possess remarkable bioactivities. Physarum polycephalum is a species of slime mold for which the microplasmodia are capable of rapid growth and can produce a significant amount of cell wall-less biomass. There has been a limited understanding of the polysaccharides produced by microplasmodia of slime molds, including P. polycephalum. Thus, the primary objectives of this research were first to chemically characterize the exopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Notably, the crude extracellular polysaccharides can be directly extracted from fungal fermentation medium by ethanol precipitation methods ( Miao et al, 2020 , Zhao et al, 2015 ). As for intracellular fungal polysaccharides, they are mainly from fruiting bodies or mycelium of fungi by different extraction methods ( Ba et al, 2020 , Do et al, 2021 , Moradi and Kalanpour, 2019 , Zhang et al, 2020a ). Before extracting intracellular fungal polysaccharides, raw materials undergo a series of pretreatment, including washing, drying, crushing, and degreasing.…”
Section: Extraction and Purification Methods Of Fungal Polysaccharidesmentioning
confidence: 99%
“…Notably, the crude extracellular polysaccharides can be directly extracted from fungal fermentation medium by ethanol precipitation methods ( Miao et al, 2020 , Zhao et al, 2015 ). As for intracellular fungal polysaccharides, they are mainly from fruiting bodies or mycelium of fungi by different extraction methods ( Ba et al, 2020 , Do et al, 2021 , Moradi and Kalanpour, 2019 , Zhang et al, 2020a ). Before extracting intracellular fungal polysaccharides, raw materials undergo a series of pretreatment, including washing, drying, crushing, and degreasing.…”
Section: Extraction and Purification Methods Of Fungal Polysaccharidesmentioning
confidence: 99%
“…is reported to induce MDA-MB cells death via apoptosis and necrosis [16]. Similarly, flow cytometric analysis of a previous study reported that fungi-derived IPS fraction induces apoptosis in human breast cancer (MCF-7) and cervical cancer (Hela) cells at 1000 µg/mL of the treatment dose [13]. Taken together, the findings of cytotoxicity analysis in PC-3 cells (Figures 8 and 9) indicated that the IPS-1 could induce apoptosis in PC-3 cells via nuclear damage associated with mitochondrial membrane potential collapse.…”
Section: Flow Cytometry Analysismentioning
confidence: 77%
“…However, the chemical shifts of the IPS-2 signals were mainly distributed in δ 3.6-4.1 and δ 5.0-5.3 (anomeric proton region) (Figure 4b). In the 13 C-NMR spectrum, the IPS-1 signals (ppm) were found at 99.82 (C1), 81.36 (C3), 74.13 (C5), 71.76 (C2), 70.38 (C4), 60.58 (C6) (Figure 4c). Similarly, the IPS-2 signals (ppm) were distributed at 102 (C1), 82.61 (C3), 76.4 (C5), 72.79 (C2), 70.34 (C4), 61.09 (C6) (Figure 4d).…”
Section: Nmr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to HeLa cells, free Dox-treated HepG2 cells demonstrated above 60% cell viability even at a high concentration (15 μg/mL) ( Figure S7B and Figure 8 B). Several studies have reported that HepG2 cells are less sensitive to Dox than HeLa cells [ 37 , 38 ]. Except for free siRNA, the viability of other samples-treated cells decreased as the concentration increased, showing their cancer cell-killing effect.…”
Section: Resultsmentioning
confidence: 99%